دراسة مستوى القدرات الإدراكية – الحركية لتلاميذ مركز محافظة بابل بعمر (12) سنة وفقا للجنس - حسين, حسن علي; كاظم, جبار علي (Sulaimani Journal for Humanities, 2018)
The introduction and the problem of research on the stages of human development on the basis of which the adoption of life for the future and at this stage is the development of the first building of the personality and through which the basic concepts are formed, as well as the safety of planning the educational process as it requires a comprehensive study of all aspects of the child's physical, mental and dynamic and emotional, Those aspects, each one affects and affects the other. Cognitive-motor abilities are one of the most important aspects that specialists have sought to study and to uncover. The study aimed at: - Detection of the level of (cognitive - motor) abilities of schoolchildren in the center of the province of Babylon at the age of (12) years. The researchers included the descriptive approach in the method of surveying and comparative studies to achieve the objectives of the study. The research community also included primary school pupils aged 12 years, male and female, and after collecting, analyzing and discussing the data, the researchers reached several conclusions, the most important of which are ( Areas of cognitive-motor abilities among male and female students. The most important recommendations. The use of cognitive (motor) capacity scales as the basis for the objective evaluation of the stages of motor development and the selection of gifted persons at the age of 12 years.